THE INFLUENCE OF DEVELOPMENT AND IMPLEMENTATION OF ISLAM TOWARD THE HAPPINESS IN INDONESIA - Akbar, Muhammad Rizal (EpistemÃƒÂ©: Jurnal Pengembangan Ilmu Keislaman, 2017)
This paper aims to seek the effect of the development and practice of Islam towards the happiness in Indonesia. Development is represented by the GrossDomestic Product (GDP) per capita variable, poverty and IPM (Human Development Index). Meanwhile, Islamic religious practice is approached from the pillars of Islam and muamalah. This study uses secondary data which provided by BPS, as well as other institutions. The 33 provinces in Indonesia had been analyzed using path analysis. The study has found that religious practice in Islam directly influences the happiness in Indonesia, whileIPM has an indirect effect on happiness, because it should be the variable of Islamic religious practice. The GDP per capita proved no effect on happiness either directly or indirectly. While poverty through religious practice on Islam has proved no effect on happiness in Indonesia. The study recommends that the principles of Islam to Indonesiaâs development must be applied in order to really be able to achieve welfare and the balance between spiritual and physical. The values of Islamic religious practice that can be used as the basic capital development because it is universal, and ensures the benefit of all (rahmatanlilaâalamin.)